DETERMINAN HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Ajeng Paradila; Nurlina; Nur Ismanidar; Meutia, Tuti (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This study aims to determine the effect of Current Ratio, Net Profit Margin, and Return on Asset on Stock Prices in Food and Beverage Companies listed on the Indonesia Stock Exchange. The data analysis method used is multiple linear regression analysis, t test, F test, and coefficient of determination analysis. Current Ratio has a positive and significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange. Net Profit Margin has a positive and significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange. Return on Asset has a positive and significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange. Current Ratio, Net Profit Margin, and Return on Asset simultaneously have a positive and significant effect on Stock Prices in food and beverage sector companies listed on the Indonesia Stock Exchange.